2017
DOI: 10.1183/13993003.01923-2016
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease in chronic obstructive pulmonary disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is independently linked to cardiometabolic morbidity and mortality. Low-grade inflammation, oxidative stress and ectopic fat, common features of chronic obstructive pulmonary disease (COPD), might contribute to the development of NAFLD.We aimed to investigate the prevalence of NAFLD and to evaluate the relationship between various types of liver damage and COPD severity, comorbidities and circulating inflammatory cytokines. Validated noninvasive tests (FibroMax: SteatoT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
65
1
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 52 publications
6
65
1
10
Order By: Relevance
“…The difference in the prevalences of NAFLD may be due to differences in the study population (eg, age and urban-dwelling area) and method (eg, ultrasonography and LFS). Additionally, in a previous study, the prevalence of OLD among 13,835 American adult subjects aged 19–80 years was 11.8%,23 and it was 13.1% in a study of 16,151 adults in Korea aged ≥40 years 24. The prevalence of OLD in this study was 8.9%.…”
Section: Discussionsupporting
confidence: 45%
“…The difference in the prevalences of NAFLD may be due to differences in the study population (eg, age and urban-dwelling area) and method (eg, ultrasonography and LFS). Additionally, in a previous study, the prevalence of OLD among 13,835 American adult subjects aged 19–80 years was 11.8%,23 and it was 13.1% in a study of 16,151 adults in Korea aged ≥40 years 24. The prevalence of OLD in this study was 8.9%.…”
Section: Discussionsupporting
confidence: 45%
“…Despite the potential two-way relationship between COPD and liver steatosis due to chronic low-grade inflammation, intermittent hypoxia and induced adipokines, 24,25 few data are available to draw an epidemiologic picture of liver steatosis in this population. In a previous study, 26 we reported that the liver fibrosis stage of non-alcoholic fatty liver disease, but not steatosis, is an independent factor of cardiovascular morbidity in COPD, in line with results in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…В декількох до-слідженнях повідомляється про зв'язок НАЖХП із функціональним станом легень, у тому числі про її асоціацію з ХОЗЛ [15][16][17][18][19][20][21].…”
Section: обговоренняunclassified
“…У цьому контексті Viglino et al [16] виявили, що НАЖХП дуже поширена у хворих на ХОЗЛ і може спричиняти кардіометаболічні супутні захворю-вання. Це проспективне когортне дослідження проведено в 111 дорослих пацієнтів із легким та Точно прогнозувати розвиток значного (≥ F2) фіброзу в пацієнтів із НАЖХП можна також за до-помогою визначення вмісту sVCAM-1 у сироватці крові [22].…”
Section: обговоренняunclassified